Dogs Don’t Die Just in Hot Cars—Exertional Heat-Related Illness (Heatstroke) Is a Greater Threat to UK Dogs - Emily J. Hall; Anne J. Carter; Dan G. O’Neill (Animals, 2020)
Heat-related illness will affect increasing numbers of dogs as global temperatures rise unless effective mitigation strategies are implemented. This study aimed to identify the key triggers of heat-related illness in dogs and investigate canine risk factors for the most common triggers in UK dogs. Using the VetCompassTM programme, de-identified electronic patient records of 905,543 dogs under primary veterinary care in 2016 were reviewed to identify 1259 heat-related illness events from 1222 dogs. Exertional heat-related illness was the predominant trigger (74.2% of events), followed by environmental (12.9%) and vehicular confinement (5.2%). Canine and human risk factors appear similar; young male dogs had greater odds of exertional heat-related illness, older dogs and dogs with respiratory compromise had the greatest odds of environmental heat-related illness. Brachycephalic dogs had greater odds of all three types of heat-related illness compared with mesocephalic dogs. The odds of death following vehicular heat-related illness (OR 1.47, p = 0.492) was similar to that of exertional heat-related illness. In the UK, exertional heat-related illness affects more dogs, and kills more dogs, than confinement in a hot vehicle. Campaigns to raise public awareness about heat-related illness in dogs need to highlight that dogs don’t die just in hot cars.